A cross-sectional population-based study on the influence of the COVID-19 pandemic on incomes in Greece - Dimitris Zavras (AIMS Press, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic induced economic shock in Greece, which translated into a decrease in household income. Thus, the objective of this study is to measure social inequality with regard to income loss due to the COVID-19 pandemic in Greece. In addition, we aim to identify the characteristics of those experiencing income loss due to the pandemic. The study uses data from the "Public Opinion in the European Union (EU) in Time of Coronavirus Crisis. Third Round" survey. The sample consists of 1036 individuals aged between 16 and 54 years. To measure inequality, the Erreygers' Concentration Index (CI) is calculated, using social class as the ranking variable. To identify the characteristics of those experiencing income loss, a logistic regression model is fitted using the region of residence and several demographic and socioeconomic variables as potential predictors. According to the results, social inequality does not exist with regard to income loss due to the COVID-19 pandemic. Thus, our findings indicate the negative influence of the pandemic on the incomes of individuals from all social classes in Greece. According to the results of the logistic regression model, the odds of experiencing income loss are higher for residents of the Aegean Islands and Crete but also for self-employed, part-time employed, and unemployed individuals. These findings indicate the negative influence of the pandemic on Greek tourism and on sectors employing a large proportion of non-standard workers. Although inequality does not exist, a substantial proportion of those losing income due to the pandemic is in line with the global picture.